2015
DOI: 10.1128/microbiolspec.mbp-0006-2014
|View full text |Cite
|
Sign up to set email alerts
|

Commensal and Pathogenic Escherichia coli Metabolism in the Gut

Abstract: E. coli is a ubiquitous member of the intestinal microbiome. This organism resides in a biofilm comprised of a complex microbial community within the mucus layer where it must compete for the limiting nutrients that it needs to grow fast enough to stably colonize. In this article we discuss the nutritional basis of intestinal colonization. Beginning with basic ecological principles we describe what is known about the metabolism that makes E. coli such a remarkably successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
163
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(170 citation statements)
references
References 119 publications
(155 reference statements)
5
163
0
2
Order By: Relevance
“…The gene expression data suggested that the luxO mutant could have metabolic defects based on the downregulation of key metabolism genes. Competition for intestinal nutrients and the ability to utilize intestinal mucus as a carbon and energy source have been shown to be important for successful colonization of intestinal bacteria (56)(57)(58)(59). Phenotypic array data showed that the deletion of luxO resulted in metabolic defects, with the mutant demonstrating a defect in growth on a number of carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression data suggested that the luxO mutant could have metabolic defects based on the downregulation of key metabolism genes. Competition for intestinal nutrients and the ability to utilize intestinal mucus as a carbon and energy source have been shown to be important for successful colonization of intestinal bacteria (56)(57)(58)(59). Phenotypic array data showed that the deletion of luxO resulted in metabolic defects, with the mutant demonstrating a defect in growth on a number of carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed different strains of E. coli appear to have different metabolic requirements for colonization, and E. coli strains with similar metabolic requirements appear to compete to occupy the same niche in the gut of the host (i.e. the restaurant hypothesis) (Conway & Cohen, 2015;Maltby et al, 2013). Previous work has also shown that gluconeogenesis and the TCA cycle are important for the growth of uropathogenic E. coli (UPEC) in urine (Alteri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, they are actually in equilibrium with the turnover rate of mucus. One possibility is explained in the "Restaurant" hypothesis, which implies that E. coli bacteria grow in synergy with gut anaerobes which can degrade large polysaccharide chains to mono-or disaccharides (34). Indeed, it was shown that commensal E. coli strain MG1655 as well as E. coli O157:H7 strain EDL933 can grow well on mucus-derived saccharides such as N-acetylglucosamine, gluconate, galactose, N-acetyl neuraminic acids, and others (39).…”
Section: Figmentioning
confidence: 99%
“…Furthermore, E. coli O157:H7 needs mechanisms to avoid host defense and to penetrate the mucus layer to reach the gut epithelium (34). Human gastrointestinal mucus consists of two layers, a thick loosely mucus layer and a thinner layer attached to the mucosa (35).…”
Section: Figmentioning
confidence: 99%